2021
DOI: 10.3390/agriculture11100919
|View full text |Cite
|
Sign up to set email alerts
|

Use of Vermicompost from Sugar Beet Pulp in Cultivation of Peas (Pisum sativum L.)

Abstract: A properly conducted vermicomposting process is an environmentally friendly technology used to transform selected organic waste into vermicompost. This organic fertilizer is increasingly used in agriculture and horticulture as an alternative to mineral fertilizers. Research has investigated the use of vermicompost made from the waste mass of sugar beet pulp as a soil additive in the cultivation of peas (Pisum sativum L.). Experimentally, five treatments consisted of: a heavy clay soil as control (SL); the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Furthermore, with the application of VC in field conditions, an increase in barley (Hordeum vulgare) yield was observed [13]. Vermicompost treatment in chickpea (Cicer arietinum) and pea (Pisum sativum) significantly increased morphological traits such as root length, stem length, and the number of leaves [14][15][16]. It was also reported that the application of VC enriched with other nutrients compared to their separate application was accompanied by improved morphological and physiological traits of the corn plant (Zea mays) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, with the application of VC in field conditions, an increase in barley (Hordeum vulgare) yield was observed [13]. Vermicompost treatment in chickpea (Cicer arietinum) and pea (Pisum sativum) significantly increased morphological traits such as root length, stem length, and the number of leaves [14][15][16]. It was also reported that the application of VC enriched with other nutrients compared to their separate application was accompanied by improved morphological and physiological traits of the corn plant (Zea mays) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, vermicomposts are produced from cattle manure with the addition of organic carbon-rich biomass, such as grass or straw [6], but it is possible to use different organic waste materials and byproducts for its production. The possibility for successful application of different types of vermicompost for the production of various crop species has been shown for vermicomposts produced from agricultural waste [7], byproducts of food production or food waste [8,9], urban organic waste [10], and composted sewage sludge [11].…”
Section: Introductionmentioning
confidence: 99%
“…Intercropping increases the absorption of photo synthetically active rays and the possibility of using the canopy space, also increases the e ciency of nutrients usage, and the relative productivity of each plant from water and nutrients increases (Hussain et al 2020;Madembo et al 2020;Maitra 2020). Vermicompost with biochar make suitable conditions for basil by providing nutrients and water and also prevent to nutrient leaching and increased soil water capacity, so they improved basil photosynthesis pigments and by increasing photosynthesis, promote soluble sugars and also yield and yield compounds of basil (Paczka et al 2021;Tavallali et al 2022). The reduction of soluble sugars reduces the nutrients needed for plant growth, and intercropping has increased the amount of soluble sugars due to the better use of organic matter in the soil by plants (Dai et al 2018).…”
Section: Discussionmentioning
confidence: 99%